RUNNING EVENT “TRACKPRESSO: 5K COLOR RUN 2024 DI KOTA SEMARANG, JAWA TENGAH” - Regita Pratitis, Penthasuci; Manalu, S. Rouli (Interaksi Online, 2024)
This project discusses the preparation and execution of the Trackpresso: 5K Color Run 2024 event. Anak Panah Kopi, as the client, collaborated with the organizing team based on a desire to host a trending event in recent months, utilizing the "riding the wave" strategy. This report follows the event management framework outlined in Joe Goldblatt's book *Special Events*, which divides the event process into five stages, from research to evaluation. Trackpresso: 5K Color Run targeted 150 participants and took place on August 24 in Semarang City. The results of this report indicate that the event was carried out in accordance with the initial target of 150 participants who attended the Trackpresso: 5K Color Run. In fulfilling the roles of Coordinator of Publications and Documentation, Marketing Manager, and Finance and Administration Manager, the team successfully managed all tasks related to publication and documentation. The Marketing Manager achieved the pre-determined Instagram follower target of 300 through promotional strategies, and the Finance and Administration Manager successfully handled all necessary paperwork and financial management for the event. This report recommends that the Trackpresso: 5K Color Run project can provide academic contributions to the preparation of similar events in the future.